2015
DOI: 10.1515/hepo-2015-0030
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of Trachystemon orientalis (L.) G. Don (Borage) grown and eaten as food in Ordu, Turkey

Abstract: SummaryIntroductıon: Instead of synthetic antioxidants, using of natural products with antioxidant activity is demanded.Objectıve: The aim of this study is to evaluate the antioxidant activity and total phenolic and flavonoid contents of theTrachystemon orientalis(borage) obtained from Ordu.Methods: The water and ethanol extracts of the borage plant were investigated by using severalin vitroantioxidant activity tests such as total antioxidant capacity, O2•−,•OH, DPPH and ABTS radicals scavenging activities, hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The difference is statistically insignificant (p=0.165). In previous studies on galdirik, the total phenolic content was 9000 mg/100 g in water extracts and 2120 mg/100 g in ethanol extracts ( 32 ). The values found in the present study are lower than those found in the literature.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The difference is statistically insignificant (p=0.165). In previous studies on galdirik, the total phenolic content was 9000 mg/100 g in water extracts and 2120 mg/100 g in ethanol extracts ( 32 ). The values found in the present study are lower than those found in the literature.…”
Section: Resultsmentioning
confidence: 90%
“…As with melocan, the water extract of galdirik had a higher antioxidant activity than the 70 % ethanol extract (p=0.165). The antioxidant activity of the water and ethanol extracts of galdirik was measured in a previous study ( 32 ) using the ABTS free radical scavenging activity assay, and the results were 1725 and 240 mmol/kg, respectively. In that study, the antioxidant concentration of this plant was comparable to that of broccoli and asparagus extracts, which had a value of 26.2 mmol/kg.…”
Section: Resultsmentioning
confidence: 99%
“…It is estimated that extracts or compounds which prevent metal-induced free radical development by inhibiting the formation of complexes between ferrozine and iron can prevent lipid peroxidation. Due to their phenolic contents, they might have chelating activity and turn the transition metals stable [35]. From this point of view, it is very important to examine our extracts in terms of chelating activities and the ability of water and ethanol extracts to compete with ferrozine to form chelates with Fe 2+ ions in the reaction medium compared with the standard chelating agent EDTA.…”
Section: Discussionmentioning
confidence: 99%
“…It was also determined to have antioxidant, antifungal and herbicide properties [1,5]. In addition to being very rich in phenolic compounds, the plant was also found to have higher antioxidant properties than asparagus and broccoli when the antioxidant activity was examined [6]. This plant is cooked and consumed in various regions of the Black Sea, stems and leaves of Trachystemon orientalis (L.) G. Don can be consumed together or separately.…”
Section: Introductionmentioning
confidence: 99%